<meta http-equiv="refresh" content="1; url=/nojavascript/">

# Special Products of Polynomials

## Work with multiple variables with special products of polynomials. Learn how to solve binomial squares, and the difference of squares with binomials.

0%
Progress
Practice Special Products of Polynomials
Progress
0%
Special Products of Polynomials

Suppose that the entrance to a dog house is a square, with a height of x\begin{align*}x\end{align*} inches and a width of x\begin{align*}x\end{align*} inches. Because your puppy has grown, you need to increase both the height and the width by 4 inches. What would be the area of the resulting entrance to the dog house? If the height had been increased by 4 inches while the width had been decreased by 4 inches, what would the area have been then? In this Concept, you'll learn about special products of polynomials so that you'll know what to do in situations like these.

### Guidance

When we multiply two linear (degree of 1) binomials, we create a quadratic (degree of 2) polynomial with four terms. The middle terms are like terms so we can combine them and simplify to get a quadratic or 2nd\begin{align*}2^{nd}\end{align*} degree trinomial (polynomial with three terms). In this Concept, we will talk about some special products of binomials.

Finding the Square of a Binomial

A special binomial product is the square of a binomial. Consider the following multiplication: (x+4)(x+4)\begin{align*}(x+4)(x+4)\end{align*}. We are multiplying the same expression by itself, which means that we are squaring the expression. This means that:

(x+4)(x+4)(x+4)(x+4)=(x+4)2=x2+4x+4x+16=x2+8x+16

This follows the general pattern of the following rule.

Square of a Binomial: (a+b)2=a2+2ab+b2\begin{align*}(a+b)^2=a^2+2ab+b^2\end{align*}, and (ab)2=a22ab+b2\begin{align*}(a-b)^2=a^2-2ab+b^2\end{align*}

Stay aware of the common mistake (a+b)2=a2+b2\begin{align*}(a+b)^2=a^2+b^2\end{align*}. To see why (a+b)2a2+b2\begin{align*}(a+b)^2 \neq a^2+b^2\end{align*}, try substituting numbers for a\begin{align*}a\end{align*} and b\begin{align*}b\end{align*} into the equation (for example, a=4\begin{align*}a=4\end{align*} and b=3\begin{align*}b=3\end{align*}), and you will see that it is not a true statement. The middle term, 2ab\begin{align*}2ab\end{align*}, is needed to make the equation work.

#### Example A

Simplify by multiplying: (x+10)2\begin{align*}(x+10)^2\end{align*}.

Solution: Use the square of a binomial formula, substituting a=x\begin{align*}a=x\end{align*} and b=10\begin{align*}b=10\end{align*}

(a+b)2(x+10)2=a2+2ab+b2=(x)2+2(x)(10)+(10)2=x2+20x+100

Finding the Product of Binomials Using Sum and Difference Patterns

Another special binomial product is the product of a sum and a difference of terms. For example, let’s multiply the following binomials.

(x+4)(x4)=x24x+4x16=x216

Notice that the middle terms are opposites of each other, so they cancel out when we collect like terms. This always happens when we multiply a sum and difference of the same terms.

(a+b)(ab)=a2ab+abb2=a2b2

When multiplying a sum and difference of the same two terms, the middle terms cancel out. We get the square of the first term minus the square of the second term. You should remember this formula.

Sum and Difference Formula: (a+b)(ab)=a2b2\begin{align*}(a+b)(a-b) = a^2-b^2\end{align*}

#### Example B

Multiply the following binomias and simplify.

(5x+9)(5x9)

Solution: Use the above formula, with a=5x\begin{align*}a=5x\end{align*} and b=9\begin{align*}b=9\end{align*}. Multiply.

(5x+9)(5x9)=(5x)2(9)2=25x281

Solving Real-World Problems Using Special Products of Polynomials

Let’s now see how special products of polynomials apply to geometry problems and to mental arithmetic. Look at the following example.

#### Example C

Find the area of the square.

Solution: The area of the square=side×side\begin{align*}The \ area \ of \ the \ square = side \times side\end{align*}.

Area=(a+b)(a+b)=a2+2ab+b2

Notice that this gives a visual explanation of the square of binomials product.

Area of big square:(a+b)2=Area of blue square=a2+2 (area of yellow)=2ab+area of red square=b2\begin{align*}Area \ of \ big \ square: (a+b)^2 = Area \ of \ blue \ square = a^2+2 \ (area \ of \ yellow) = 2ab + area \ of \ red \ square = b^2\end{align*}

The next example shows how to use the special products in doing fast mental calculations.

#### Example D

Find the products of the following numbers without using a calculator.

(a) 43×57\begin{align*}43 \times 57\end{align*}

(b) 452\begin{align*}45^2\end{align*}

Solution: The key to these mental “tricks” is to rewrite each number as a sum or difference of numbers you know how to square easily.

(a) Rewrite 43=(507)\begin{align*}43=(50-7)\end{align*} and 57=(50+7)\begin{align*}57=(50+7)\end{align*}.

Then 43×57=(507)(50+7)=(50)2(7)2=250049=2,451\begin{align*}43 \times 57 = (50-7)(50+7) = (50)^2-(7)^2=2500-49=2,451\end{align*}.

(b) 452=(40+5)2=(40)2+2(40)(5)+(5)2=1600+400+25=2,025\begin{align*}45^2 = (40+5)^2 = (40)^2+2(40)(5) +(5)^2 = 1600+400+25=2,025\end{align*}

-->

### Guided Practice

Multiply (2x+3y)(2x3y)\begin{align*}(2x+3y)(2x-3y)\end{align*}.

Solution:

In order to get the hang of the patterns involved in special products, apply the distributive property to see what will happen:

(2x+3y)(2x3y)2x(2x3y)+3y(2x3y)2x(2x)+2x(3y)+3y(2x)+3y(3y)4x26xy+6xy9y24x29y2====

Notice how the two middle terms canceled each other out. This always happens, which is where we get the sum and difference product. Compare the answer above to that from using the sum and difference product:

(a+b)(ab)=a2b2(2x+3y)(2x3y)=(2x)2(3y)2=22x232y2=4x29y2\begin{align*}(a+b)(a-b) = a^2-b^2 \Rightarrow (2x+3y)(2x-3y)=(2x)^2-(3y)^2=2^2x^2-3^2y^2=4x^2-9y^2\end{align*}

The two answers are the same. You can use the sum and difference product as a shortcut, so you don't always have to go through the whole process of multiplying out using the distributive property.

### Explore More

Sample explanations for some of the practice exercises below are available by viewing the following video. Note that there is not always a match between the number of the practice exercise in the video and the number of the practice exercise listed in the following exercise set. However, the practice exercise is the same in both. CK-12 Basic Algebra: Special Products of Binomials (10:36)

Use the special product for squaring binomials to multiply these expressions.

1. (x+9)2\begin{align*}(x+9)^2\end{align*}
2. (x1)2\begin{align*}(x-1)^2\end{align*}
3. (2y+6)2\begin{align*}(2y+6)^2\end{align*}
4. (3x7)2\begin{align*}(3x-7)^2\end{align*}
5. (7c+8)2\begin{align*}(7c+8)^2\end{align*}
6. (9a2+6)2\begin{align*}(9a^2+6)^2\end{align*}
7. (b21)2\begin{align*}(b^2-1)^2\end{align*}
8. (m3+4)2\begin{align*}(m^3+4)^2\end{align*}
9. (14t+2)2\begin{align*}\left ( \frac{1}{4} t+2 \right )^2\end{align*}
10. (6k3)2\begin{align*}(6k-3)^2\end{align*}
11. (a37)2\begin{align*}(a^3-7)^2\end{align*}
12. (4x2+y2)2\begin{align*}(4x^2+y^2)^2\end{align*}
13. (8x3)2\begin{align*}(8x-3)^2\end{align*}

Use the special product of a sum and difference to multiply these expressions.

1. \begin{align*}(2x-1)(2x+1)\end{align*}
2. \begin{align*}(2x-3)(2x+3)\end{align*}
3. \begin{align*}(4+6x)(4-6x)\end{align*}
4. \begin{align*}(6+2r)(6-2r)\end{align*}
5. \begin{align*}(-2t+7)(2t+7)\end{align*}
6. \begin{align*}(8z-8)(8z+8)\end{align*}
7. \begin{align*}(3x^2+2)(3x^2-2)\end{align*}
8. \begin{align*}(x-12)(x+12)\end{align*}
9. \begin{align*}(5a-2b)(5a+2b)\end{align*}
10. \begin{align*}(ab-1)(ab+1)\end{align*}

Find the area of the red square in the following figure. It is the lower right shaded box.

Multiply the following numbers using the special products.

1. \begin{align*}45\times 55\end{align*}
2. \begin{align*}97 \times 83\end{align*}
3. \begin{align*}19^2\end{align*}
4. \begin{align*}56^2\end{align*}
5. \begin{align*}876 \times 824\end{align*}
6. \begin{align*}1002 \times 998\end{align*}
7. \begin{align*}36 \times 44\end{align*}

### Vocabulary Language: English Spanish

Square of a Binomial

Square of a Binomial

The product of a squared binomial is always a trinomial.
sum and difference formula

sum and difference formula

$(a+b)(a-b) = a^2-b^2$
Binomial

Binomial

A binomial is an expression with two terms. The prefix 'bi' means 'two'.